2019
DOI: 10.1002/tsm2.103
|View full text |Cite
|
Sign up to set email alerts
|

Persistent functional loss following ruptured Achilles tendon is associated with reduced gastrocnemius muscle fascicle length, elongated gastrocnemius and soleus tendon, and reduced muscle cross‐sectional area

Abstract: We examined muscle function, muscle architecture, and tendon length bilaterally in persons who experience a functional deficit 2 years after an Achilles tendon rupture. Eleven persons were investigated on the injured compared with the uninjured side 47 ± 7 months (mean ± SD) after a tendon rupture. Heel‐rise data, plantar flexion strength, tendon resting angle 3D MRI‐determined tendon length and muscle cross‐sectional area, ultrasound‐determined fascicle length, and pennation angle were obtained. The heel‐rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 56 publications
8
39
2
2
Order By: Relevance
“…Although the changes in muscle and tendon thickness post rupture were somewhat expected, the significant increases in fascicle pennation and decreases in fascicle length in the injured limb demonstrate the multi-faceted nature of muscle-tendon function and highlight the need to consider tissue quality as well as tissue quantity. Skeletal muscle has been shown to remodel is response to alterations in surrounding structures in animal models [29,30] and whilst changes in plantar flexor architecture have been recently observed in humans following Achilles tendon rupture [16,18,19], this study highlights the long-lasting nature of these changes. It seems likely that the changes in fascicle pennation and length may have occurred as one of many compensatory mechanisms to the loss in muscle size.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Although the changes in muscle and tendon thickness post rupture were somewhat expected, the significant increases in fascicle pennation and decreases in fascicle length in the injured limb demonstrate the multi-faceted nature of muscle-tendon function and highlight the need to consider tissue quality as well as tissue quantity. Skeletal muscle has been shown to remodel is response to alterations in surrounding structures in animal models [29,30] and whilst changes in plantar flexor architecture have been recently observed in humans following Achilles tendon rupture [16,18,19], this study highlights the long-lasting nature of these changes. It seems likely that the changes in fascicle pennation and length may have occurred as one of many compensatory mechanisms to the loss in muscle size.…”
Section: Discussionmentioning
confidence: 64%
“…Specifically, the observed increases in fibre pennation may have facilitated increased fibre density [31] and tendon tension whilst decreases in fascicle length may have served to restore resting tension caused by tendon elongation [16,18]. In terms of fascicle length, Svensson et al [19] showed significant reductions (18%) in fascicle length of the medial gastrocnemius 2 years after Achilles tendon rupture with the authors highlighting the importance of this change with respect to the capacity to perform dynamic movements effectively. Although the consequences of greater pennation cannot be fully appreciated through two-dimensional ultrasonography, the trends towards tendon elongation in the injured limb and associations between Achilles tendon length and fibre length asymmetries are supportive of such outcomes [32,28].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, higher triceps surae activation has been seen in individuals with tendon elongation during gait and tendon material properties during jumping tasks. Both experimental and modeling studies support the notion that both muscle fiber length and tendon elongation factor into heel rise height . It seems that there is an interplay between the tendinous and muscular contributions of the triceps surae that can compensate for some amount of dysfunction of the individual components.…”
Section: Introductionmentioning
confidence: 64%
“…One explanation for the difference in athletic performance is that non-operative management following Achilles tendon rupture may encourage early rehabilitation that leads to tendon elongation and reduced force production in the long term. 65,66 Since arguments could be made for and against surgery following an Achilles tendon rupture, shared decision making will assist athletes understand the benefits and potential harms of each approach and ensure they are able to make an informed choice.…”
Section: Surgerymentioning
confidence: 99%